2023
DOI: 10.1007/s00105-023-05150-5
|View full text |Cite
|
Sign up to set email alerts
|

Zoophile Dermatophyten während der Corona-Pandemie in Deutschland

Abstract: Während der Corona-Pandemie wurden deutlich mehr Haustiere gekauft und gehalten. Ob in der Folge auch mehr zoophile Dermatophyten isoliert wurden und welche Spezies im Vordergrund standen, stand im Fokus dieser Untersuchung. Im Zeitraum von einem Jahr, von März 2020 bis Februar 2021, wurden die zoophilen Dermatophyten aus allen Einsendungen im Labor Mölbis erfasst. Berücksichtigt wurden sowohl der kulturelle als auch der molekulare Pilznachweis direkt aus Hautschuppen, Haarwurzeln, im Einzelfall aus Nägeln. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Zoophilic dermatophytes were increasingly isolated during the coronavirus pandemic in Germany. T. benhamiae and T. quinckeanum are emerging pathogens from guinea pigs, mice and other pets found in children 60 . Very rarely, moulds like Aspergillus protuberus are responsible.…”
Section: Fungal Species Associated With Kerion Celsimentioning
confidence: 99%
See 2 more Smart Citations
“…Zoophilic dermatophytes were increasingly isolated during the coronavirus pandemic in Germany. T. benhamiae and T. quinckeanum are emerging pathogens from guinea pigs, mice and other pets found in children 60 . Very rarely, moulds like Aspergillus protuberus are responsible.…”
Section: Fungal Species Associated With Kerion Celsimentioning
confidence: 99%
“…Very rarely, moulds like Aspergillus protuberus are responsible. Table 1 provides an overview on published cases in English and German between the years 2010 and 2023 4–60 …”
Section: Fungal Species Associated With Kerion Celsimentioning
confidence: 99%
See 1 more Smart Citation
“…In a large German center, T . benhamiae is the most frequent zoophilic species isolated in human infections, especially in children [ 55 ]. The emergence of T .…”
Section: Introductionmentioning
confidence: 99%
“…mentagrophytes , ahead of M . canis , accounting for 19.0% of human zoonotic infections [ 55 ]. Recent reports confirmed that in addition to previously recognized reservoirs ( i.e.…”
Section: Introductionmentioning
confidence: 99%